Lidar observations of large-amplitude mountain waves in the stratosphere above Tierra del Fuego, Argentina - Kaifler, N. (2020)
Large-amplitude internal gravity waves were observed using Rayleigh lidar temperature soundings above Rio Grande, Argentina (54◦ S, 68◦ W), in the period 16–23 June 2018.Temperature perturbations in the upper stratosphere amounted to 80 K peak-to-peak and potential energy densities exceeded 400 J/kg.The measured amplitudes and phase alignments agree well with operational analyses and short-term forecasts of the Integrated Forecasting System (IFS) of the European Centre for Medium-Range Weather Forecasts (ECMWF), implying that these quasi-steady gravity waves resulted from the airfow across theAndes.We estimate gravity wave momentum fuxes larger than 100 mPa applying independent methods to both lidar data and IFS model data. These mountain waves deposited momentum at the inner edge of the polar night jet and led to a long-lasting deceleration of the stratospheric fow.The accumulated mountain wave drag afected the stratospheric circulation several thousand kilometers downstream. In the 2018 austral winter, mountain wave events of this magnitude contributed more than 30% of the total potential energy density, signifying their importance by perturbing the stratospheric polar vortex.